ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INHALASI AROMATERAPI LEMON DAN PEPPERMINT UNTUK MENURUNKAN EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I - Rifdah Camila (2023)
Pregnancy is a natural (physiological) process experienced by a woman. Every process of pregnancy is a crisis situation that requires physiological and psychological adaptation. Changes that occur in pregnant women can cause discomfort during pregnancy, including nausea and vomiting or emesis gravidarum in the early stages of pregnancy. One of the complementary therapies that can reduce emesis gravidarum is aromatherapy inhalation. Types of aromatherapy that have a therapeutic effect in relieving nausea and vomiting are the aromas of lemon and peppermint. Purpose: To analyze nursing care with lemon and peppermint aromatherapy inhalation interventions to reduce emesis gravidarum in first-trimester pregnant women. Method: This study uses the case study method with the application of evidence-based nursing in nursing care for two patients with emesis gravidarum. The instrument used as a measure of nausea and vomiting in pregnant women uses PUQE-24. Results: There was a decrease in the intensity of nausea and vomiting felt by pregnant women in the first trimester after inhaling lemon and peppermint aromatherapy from NVP 6 to NVP 4 in managed patients and from NVP 7 to NVP 4 in resume patients. Conclusion: Lemon and peppermint aromatherapy inhalation has effectiveness in reducing emesis gravidarum in first-trimester pregnant women.